Population density drives increased parasitism via greater exposure and reduced resource availability in wild red deer - Adam Z. Hasik; Shane Butt; Katie Maris; Sean Morris; Alison Morris; Richard S. Turner; Josephine M. Pemberton; Gregory F. Albery (Parasitology)
Exposure to environmentally transmitted parasites should increase with population density due to accumulation of infective parasites in space. However, resource competition also increases with density, lowering immunity and increasing susceptibility, offering an alternative pathway for density-dependent infection. To test the relationships between these two processes and parasitism, we examined associations between host density, resource availability, immunity, and counts of 3 common helminth parasites using a long-term study of red deer. We found evidence that immunity increased with resource availability while parasite counts declined with immunity. We also found that greater density correlated with reduced resource availability, and while density was positively associated with both strongyle and tissue worm burdens, resource availability was independently and negatively associated with the same burdens. Our results support separate roles of density-dependent exposure and susceptibility in driving infection, providing evidence that resource competition is an important driver of infection, exacerbating effects of density-dependent increases in exposure.